Food Studies and Disability Studies: Introducing a Happy Marriage - Elaine Gerber (Disability Studies Quarterly, 2007)
Food Studies scholarship has yet to make the notion of "disability" central to its analyses. At the same time, Disability Studies scholarship, with its long tradition of examining the social, cultural, and environmental nature of disability, and its emphasis on inclusion and exclusion, has yet to make food and eating a core focus for analysis. Articles in this volume address the site of intersection between these two fields, utilizing a variety of approaches and from a variety of disciplines.
Keywords: Food Studies; Disability Studies; Food; Eating; Disability